A preliminary study of the breeding biology of Ross's Goose - Ryder, John P (Wildfowl, 1964)
Studies of a breeding colony of Ross's Goose in the Perry River region, N.W.T. from June to August, 1963 are reported. The first geese arrived on 5th June, probably about 10 days later than usual. The first eggs were laid on 9th June. No courtship was seen and copulation probably occurred somewhere further south. Nests are made on islands in lakes, preferably in cover provided by scrub or rocks. Nests on open moss are larger than those in sheltered places. Nesting territories, which were fiercely defended, may be as small as 150 sq. ft. Eggs are usually laid daily. The average size of 769 clutches was 3.67, range 1-6 eggs. Egg size did not vary with sequence in the clutch. The female alone incubates for 23-24 days from the laying of the last egg. 90 of 93 nests (96.7%) were successful, and 93.5% of eggs laid hatched. Though the goslings are polymorphic, 75% of broods were monomorphic. 1963 was mild but in some years bad weather may be a serious mortality factor. Some goslings died after being trapped in bushes or in crevices. Predation, by gulls and jaegers, is slight. There was an unexpected excess of males in yearlings caught for banding.